Research on the edge-end collaboration framework for deterministic network - Guangmin SONG; Qunqing WANG; Zhanbing HUANG; Xun SHI; Gaojian HAN (Dianxin kexue)
5G vertical industries such as industrial automatic control have strict requirements on network transmission delay and reliability.It was focused on the AGV collaborative carrying scenarios, in which the key quality indicator (KQI) of the AGV collaboration and the requirements for network jitter were analyzed.Existing 5G ultra-low-latency technologies, such as the pre-scheduling mechanism, reduce transmission scheduling latency by reserving a large number of time-frequency resources, which heavily decreases spectrum efficiency.In addition, wireless channel quality factors such as weak coverage and interference, often cause large jitter, making it difficult to meet the service reliability requirements.In order to deal with these challenges, a deterministic edge-end cooperation framework design to guarantee end-to-end latency was proposed.Based on service flow characteristics, resource reservation was utilized to reduce scheduling latency.Moreover, the proposed framework could enhance data transmissions when poor status of channels was sensed.The experimental results show that the edge-end collaboration framework design can effectively increase the delay reliability, reduce the large jitter, and improve the KQI of AGV collaboration.